The Development of Cyber Counseling as a Counseling Service Model for High School Students in the Digital Age - Gading, I Ketut (Jurnal Pendidikan Indonesia, 2020)
This research aimed at developing theoretical models and guidelines for cyber counseling, as well as examining their acceptability and effectiveness. The stages of the study consisted of 4 D namely define, design, develop, and disseminate. The acceptance test involved 2 experts as reviewers, while the effectiveness test involved 30 high school students as participants. The effectiveness of models and guidelines was measured by participants' responses to the benefits of cyber counseling. Data were collected using questionnaires and then analyzed using a t-test. Results showed that the theoretical model of cyber counseling consisted of raw input, instrumental input, environmental input, process, and counseling goals. The guidelines for cyber counseling were set out in the steps of cyber counseling consisting of initial communication, internalization, and termination. The acceptance of the model and cyber counseling guidelines was very high with a coefficient of 1.00. Therefore, cyber counseling should be used as a model of counseling services for high school students in the digital age effectively.